Composite coated cutting tool and method of making same

CN122979829APending Publication Date: 2026-10-27GANZHOU ACHTECK TOOL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611490028.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

传统AlCrN基硬质涂层,硬度与韧性难以兼顾;单一成分涂层,切削高温下晶粒易长大,抗氧化能力受限;常规多层涂层成分突变,层间内应力大,裂纹易沿层间扩展,膜-基结合强度不足

Benefits of technology

[0011]上述方法采用多弧离子镀技术,该技术简单、操作方便,且利于实现梯度复合层的成分梯度变化、厚度梯度变化以及晶型的梯度变化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979829A_ABST
    Figure CN122979829A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of surface protection coating, and particularly relates to a composite coating cutter and a preparation method thereof. The composite coating cutter comprises a base body and a functional coating. The functional coating comprises, in sequence in a direction away from the base body, a Cr adhesive layer, a CrN transition layer, an AlCrVN support layer, a gradient composite layer and an AlCrTaN surface layer. The gradient composite layer comprises a plurality of sub-coating layers arranged in a stack. Each sub-coating layer comprises an AlCrVN sub-coating layer and an AlCrSiBN sub-coating layer. The gradient composite layer satisfies the following conditions: the atomic percentage of V gradually decreases; the atomic percentages of Si and B gradually increase; the crystal morphology continuously transitions from columnar crystals to equiaxed crystals, and the volume fraction of amorphous phase gradually increases; the single-layer thickness of the AlCrVN sub-coating layer gradually decreases; and the single-layer thickness of the AlCrSiBN sub-coating layer gradually increases. The composite coating cutter has good wear resistance, ultrahigh film-substrate bonding strength and excellent high-temperature oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of surface protective coating technology, specifically relating to composite coated cutting tools and their preparation methods. Background Technology

[0002] During metal cutting, cutting tools are continuously subjected to multiple effects, including mechanical impact, friction and wear, high-temperature oxidation, and workpiece adhesion. Under cutting conditions, the coating near the substrate needs good toughness and interfacial bonding, while the surface layer requires high hardness, oxidation resistance, and anti-adhesion properties. Traditional AlCrN-based hard coatings struggle to balance hardness and toughness; single-component coatings are prone to grain growth at high cutting temperatures, limiting oxidation resistance; conventional multilayer coatings exhibit abrupt compositional changes, resulting in high interlayer stress, easy crack propagation along interlayer boundaries, and insufficient film-substrate bonding strength. Existing coating systems cannot adequately meet the requirements of high wear resistance, excellent toughness, strong film-substrate bonding, and good high-temperature oxidation resistance in high-speed cutting of titanium alloys. Therefore, cutting tools require further improvement. Summary of the Invention

[0003] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, this invention proposes a composite coated cutting tool with good wear resistance, ultra-high film-substrate bonding strength, and excellent high-temperature oxidation resistance, as well as a method for its preparation.

[0004] A first aspect of this application provides a composite coated cutting tool, comprising: a substrate and a functional coating disposed on the surface of the substrate, the functional coating comprising: A Cr adhesive layer is disposed on the surface of the substrate; A CrN transition layer is disposed on the surface of the Cr adhesive layer away from the substrate; An AlCrVN support layer is disposed on the surface of the CrN transition layer away from the substrate; A gradient composite layer includes multiple stacked sub-coatings, each of which includes an AlCrVN sub-coating and an AlCrSiBN sub-coating, wherein the AlCrVN sub-coating is disposed close to the AlCrVN support layer; An AlCrTaN surface layer is disposed on the surface of the gradient composite layer away from the substrate; Wherein, in the direction away from the substrate, the gradient composite layer satisfies: The atomic percentage of V gradually decreases; The atomic percentages of Si and B each increase gradually and independently; The crystal morphology transitions continuously from columnar to equiaxed crystals, and the volume fraction of the amorphous phase gradually increases. The thickness of a single layer of the AlCrVN sub-coating gradually decreases; The thickness of the single layer of the AlCrSiBN sub-coating gradually increases; The volume fraction of the amorphous phase is calculated based on the total volume fraction of the crystalline phase and the amorphous phase.

[0005] According to embodiments of this application, the composite coated cutting tool satisfies at least one of the following conditions: In the direction away from the substrate, in the gradient composite layer, the atomic percentage of V, calculated based on the total number of atoms in a single AlCrVN sub-coating, gradually decreases from 2 at.% to 5 at.% to 0. In the direction away from the substrate, in the gradient composite layer, the atomic percentage of Si gradually increases from 0 to 3.5 at.%~5 at.% based on the total number of atoms in a single AlCrSiBN sub-coating. In the direction away from the substrate, in the gradient composite layer, the atomic percentage of B gradually increases from 0 to 1.5 at.% to 2.5 at.%, based on the total number of atoms in a single AlCrSiBN sub-coating.

[0006] According to embodiments of this application, the composite coated cutting tool satisfies at least one of the following conditions: The amorphous phase includes Si3N4 phase and BN phase; In the direction away from the matrix, based on the total volume of the crystalline phase and the amorphous phase, the volume fraction of the amorphous phase in the gradient composite layer continuously increases from 2%~5% to 12%~18%; In the direction away from the matrix, the grain size in the crystalline phase decreases continuously from 50 nm to 80 nm to 10 nm to 25 nm; The gradient composite layer includes a nanocomposite structure, and the nanocomposite structure includes AlCrN grains coated with an amorphous phase.

[0007] According to embodiments of this application, the composite coated cutting tool satisfies at least one of the following conditions: The thickness of the Cr bonding layer is 0.05 μm to 0.15 μm; The thickness of the CrN transition layer is 0.15 μm to 0.35 μm; The thickness of the AlCrVN support layer is 0.5μm~1μm; The thickness of the gradient composite layer is 1μm~4μm; The thickness of each AlCrVN sub-coating and each AlCrSiBN sub-coating is independently 5 nm to 30 nm; The thickness of the AlCrTaN surface layer is 0.3 μm to 0.5 μm.

[0008] According to embodiments of this application, the composite coated cutting tool satisfies at least one of the following conditions: The AlCrVN support layer has a columnar crystal structure; In the AlCrVN support layer, the atomic ratio between the metal elements Al, Cr and V is (60~68):(28~30):(4~10), and the atomic ratio between the metal elements Al, Cr and V and N satisfies: 0.9≤(Al+Cr+V) / N≤1.1; The surface roughness Ra of the AlCrTaN surface layer on the side away from the substrate is less than 0.15 μm; The surface layer of AlCrTaN has an equiaxed crystal structure; In the AlCrTaN surface layer, the atomic ratio between the metal elements Al, Cr and Ta is (57~68):(24~30):(6~15), and the atomic ratio between the metal elements and the N element satisfies: 0.9≤(Al+Cr+Ta) / N≤1.1; In the gradient composite layer, in the AlCrSiBN sub-coating adjacent to the AlCrTaN surface layer, based on the total number of atoms in a single AlCrSiBN sub-coating, the atomic percentage of Si is 3.5 at.% to 5 at.%, and the atomic percentage of B is 1.5 at.% to 2.5 at.%.

[0009] According to embodiments of this application, the composite coated cutting tool satisfies at least one of the following conditions: In the functional coating, the region with columnar crystal morphology is called the columnar crystal region, and the total thickness of the columnar crystal region is 1μm~2μm; In the functional coating, the region with equiaxed crystal morphology is called the equiaxed crystal region, and the total thickness of the equiaxed crystal region is 1μm~4μm; The total thickness of the functional coating is 2μm~6μm; The fracture toughness of the functional coating is 4.5 MPa·m. 1 / 2 ~5.5 MPa·m 1 / 2 ; The functional coating has a first end and a second end, the hardness of the surface of the first end increases monotonically from the hardness of the surface of the second end, and the hardness of the surface of the first end is 28GPa~32GPa, and the hardness of the surface of the second end is 33GPa~37GPa. The first end is the surface of the AlCrVN support layer away from the substrate, and the second end is the surface of the AlCrTaN surface layer away from the substrate.

[0010] A second aspect of this application provides a method for preparing the composite coated cutting tool described in the first aspect, comprising: Provide a matrix; In a pure Ar atmosphere, using a pure Cr target as the deposition source, a Cr binder layer is deposited on the surface of the substrate to obtain the first product. In a pure N2 atmosphere, using a pure Cr target as the deposition source, a CrN transition layer is deposited on the surface of the first product to obtain the second product; In a pure N2 atmosphere, using an AlCrV target as the deposition source, an AlCrVN support layer is deposited on the surface of the second product to obtain the third product. In a pure N2 atmosphere, using AlCrV and AlCrSiB targets as deposition sources, the AlCrV and AlCrSiB targets are deposited alternately while the target current of the AlCrV target is gradually reduced until it is turned off, and the target current of the AlCrSiB target is gradually increased, along with the deposition bias voltage. Through the alternating deposition of the AlCrV and AlCrSiB targets, AlCrVN and AlCrSiBN sub-coatings are sequentially formed, forming a gradient composite layer to obtain the fourth product. In a pure N2 atmosphere, using an AlCrTa target as the deposition source, an AlCrTaN surface layer is deposited on the surface of the fourth product to obtain a composite coated tool.

[0011] The above method uses multi-arc ion plating technology, which is simple, easy to operate, and conducive to achieving gradient changes in composition, thickness, and crystal form of the gradient composite layer.

[0012] According to an embodiment of this application, in a pure N2 atmosphere, using an AlCrV target as the deposition source and an AlCrSiB target, the AlCrV target and the AlCrSiB target are deposited alternately, and the bias voltage is controlled to increase linearly from -60V to -80V to -100V to -120V. The target current of the AlCrV target decreases linearly from 150A to 200A to 50A and is then turned off; the target current of the AlCrSiB target increases linearly from 50A to 150A to 200A and is then normally turned on, resulting in a fourth product.

[0013] According to embodiments of this application, the above method satisfies at least one of the following conditions: The temperature at which the Cr bonding layer is deposited is 450℃~550℃; The bias voltage of the deposited Cr bonding layer is -120V to -180V; When depositing the Cr binder layer, the target current of the pure Cr target is 130A~160A; The gas pressure of the deposited Cr binder layer is 0.2 Pa to 1.0 Pa; The temperature at which the CrN transition layer is deposited is 450℃~550℃; The bias voltage of the deposited CrN transition layer is -40V to -60V; When depositing the CrN transition layer, the target current of the pure Cr target is 130A~160A; The gas pressure of the deposited CrN transition layer is 2.5 Pa to 4.0 Pa; The temperature at which the AlCrVN support layer is deposited is 450℃~550℃; The bias voltage of the deposited AlCrVN support layer is -40V to -60V; When depositing the AlCrVN support layer, the AlCrV target current is 150A~200A; The gas pressure of the deposited AlCrVN support layer is 2.5 Pa to 4.0 Pa; The temperature at which the AlCrTaN surface layer is deposited is 450℃~550℃; The bias voltage of the deposited AlCrTaN surface layer is -80V to -120V; When depositing the AlCrTaN surface layer, the target current of the AlCrTa target is 150A~200A; The gas pressure of the deposited AlCrTaN surface layer is 2.5 Pa to 4.0 Pa.

[0014] According to an embodiment of this application, after obtaining the fourth product, the process further includes Ar ion etching on the surface of the AlCrSiBN sub-coating for a time of 5 min to 10 min. Attached Figure Description

[0015] Figure 1 This is a schematic diagram of the structure of a composite coated cutting tool according to an embodiment of this application.

[0016] Figure label: 100 - Substrate; 200 - Cr adhesive layer; 300 - CrN transition layer; 400 - AlCrVN support layer; 500 - Gradient composite layer; 510 - AlCrVN sub-coating; 520 - AlCrSiBN sub-coating; 600 - AlCrTaN surface layer. Detailed Implementation

[0017] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0018] With the rapid development of the aerospace industry, titanium alloys, with their high specific strength, excellent corrosion resistance, and comprehensive mechanical properties, have become an indispensable core structural material in extreme service environments. Titanium alloys themselves are characterized by high strength, high plasticity, and extremely low thermal conductivity, making them a recognized difficult-to-machine material. In actual milling and turning operations, they present several significant challenges: heat is difficult to dissipate during cutting, keeping the tool tip area at a continuously high temperature; the material is highly chemically reactive, easily undergoing atomic interdiffusion with the tool surface, forming stubborn built-up edge and tool adhesion; simultaneously, titanium alloys exhibit significant work hardening, subjecting the tool-chip interface to alternating frictional and impact loads. These multiple factors combined result in rapid tool wear, poor surface finish, and difficulty in guaranteeing dimensional accuracy. Under high-speed, heavy-load cutting conditions, the contact area between the tool and the workpiece is simultaneously subjected to extremely high frictional stress and thermal stress. High temperature will soften the coating substrate, reduce the coating hardness and structural strength. The coupled effect of high temperature, mechanical load and high cutting speed will also promote the initiation of microcracks in the coating. After gradual expansion, it will cause brittle spalling of the coating and chipping of the cutting edge, ultimately leading to premature tool failure, which seriously restricts the processing efficiency and production cost control of titanium alloys.

[0019] Currently, several physical vapor deposition (PVD) coating systems have been developed both domestically and internationally for titanium alloy machining, but each coating has varying degrees of performance limitations. AlTiN coating is the most mature nitride coating for industrial application, exhibiting good overall service performance due to its balanced hardness and wear resistance, as well as the dense alumina film formed at high temperatures. However, this coating contains titanium, resulting in high chemical compatibility with titanium alloy workpieces. This leads to easy adhesion at the cutting interface, causing built-up edge fluctuations in cutting force, workpiece surface scratches, and even tool chipping, failing to meet the high-precision, long-life machining requirements of titanium alloys. TiB2 coatings prepared by magnetron sputtering have a relatively smooth surface and low coefficient of friction, reducing friction between the tool and workpiece and improving surface quality. However, TiB2 coatings have poor oxidation resistance and also cannot meet the long-life machining requirements of titanium alloys. Traditional AlCrN coatings, due to their lack of Ti, significantly outperform AlTiN in anti-adhesion and high-temperature oxidation resistance when machining titanium alloys. However, their low hardness and tendency to decompose into Cr2N at high temperatures also make them unsuitable for titanium alloy machining.

[0020] In summary, existing coating systems are insufficient to simultaneously meet the requirements of high wear resistance, excellent toughness, strong film-substrate adhesion, and good resistance to high-temperature oxidation in high-speed cutting of titanium alloys. Therefore, there is an urgent need to develop a novel tool coating that integrates these multiple functions to meet the stringent conditions of high-speed cutting of titanium alloys.

[0021] Based on the above, the first aspect of this application refers to... Figure 1A composite coated cutting tool is proposed, comprising: a substrate 100 and a functional coating disposed on the surface of the substrate 100, the functional coating comprising: A Cr adhesive layer 200 is disposed on the surface of the substrate; A CrN transition layer 300 is disposed on the surface of the Cr adhesive layer away from the substrate; An AlCrVN support layer 400 is disposed on the surface of the CrN transition layer away from the substrate; The gradient composite layer 500 includes a plurality of stacked sub-coatings 50, each of the sub-coatings including an AlCrVN sub-coating 510 and an AlCrSiBN sub-coating 520, wherein the AlCrVN sub-coating 510 is disposed close to the AlCrVN support layer 400. An AlCrTaN surface layer 600 is disposed on the surface of the gradient composite layer away from the substrate; Wherein, in the direction away from the substrate 100, the gradient composite layer 500 satisfies: The atomic percentage of V gradually decreases; The atomic percentages of Si and B each increase gradually and independently; The crystal morphology transitions continuously from columnar to equiaxed crystals, and the volume fraction of amorphous phase increases continuously. The thickness of a single layer of the AlCrVN sub-coating gradually decreases; The thickness of the single layer of the AlCrSiBN sub-coating gradually increases; The volume fraction of the amorphous phase is calculated based on the total volume fraction of the crystalline phase and the amorphous phase.

[0022] The composite coated cutting tool of this application exhibits good wear resistance, good toughness, excellent film-substrate bonding strength, and good resistance to high-temperature oxidation. Specific characteristics are as follows: (1) Excellent high-temperature self-lubricating properties: The AlCrVN support layer and AlCrVN sub-coating will generate VO under high-temperature friction. X The oxide can form a lubricating layer at the tool-chip interface, reduce interfacial friction and heat generation, achieve a self-lubricating effect, and extend the service life of the tool.

[0023] (2) Ultra-high hardness and wear resistance: The Si and B elements in the AlCrSiBN sub-coating can promote the formation of amorphous phases, resulting in a significant increase in hardness. In addition, the gradient composite layer can further improve the hardness. In the AlCrTaN surface layer, the addition of Ta element further enhances the red hardness of the coating, enabling the functional coating to maintain high hardness at high temperatures.

[0024] (3) Excellent fracture toughness: In the triple gradient alternating structure of composition gradient, crystal form gradient and thickness gradient, the crack deflection effect in the columnar crystal-equiaxed crystal transition zone (high AlCrVN content easily forms columnar crystals, while high AlCrSiBN content easily forms equiaxed crystals), and the large number of layered interfaces between the alternating AlCrVN sub-coatings and AlCrSiBN sub-coatings, cause the cracks to continuously deflect and branch during the propagation process, greatly improving the fracture toughness of the functional coating and effectively preventing the functional coating from peeling off and chipping. The triple gradient design makes the hardness increase along the depth direction, achieving an ideal match of high surface hardness and high internal toughness. There are no abrupt interfaces between the layers, and the continuous transition of composition eliminates interlayer stress concentration.

[0025] (4) Extremely strong adhesion: The gradient design of the Cr bonding layer and the CrN transition layer ensures excellent adhesion between the coating and the substrate; the CrN transition layer and the AlCrVN support layer form a consistent crystal structure, enabling epitaxial growth and significantly improving the interlayer bonding strength. In addition, the functional coating is based on AlCrN material, and moderate interdiffusion of elements can occur between the functional layers under high-temperature cutting conditions, further improving the overall bonding strength. At the same time, Ta, Si, B and other elements are doped into each functional coating component, which can increase the decomposition temperature of the AlCrN-based coating, thereby improving the overall high-temperature stability.

[0026] (5) Excellent high-temperature oxidation resistance: The functional coating contains a high content of Al and Cr elements, which will generate Al2O3 and Cr2O3 under high temperature conditions, forming a stable and dense composite protective film. The amorphous phase in the functional coating can fill the grain boundary and hinder the diffusion channel of oxygen atoms, thus significantly improving the oxidation resistance of the functional coating.

[0027] According to embodiments of this application, the substrate material includes at least one of cemented carbide, cubic boron nitride (CBN), cermet, and ceramic. This type of substrate possesses excellent properties, providing mechanical support for the functional coating and exhibiting good interfacial compatibility with the functional coating.

[0028] According to embodiments of this application, in the gradient composite layer 500, in the direction away from the substrate, the atomic percentage of V, calculated based on the total number of atoms in a single AlCrVN sub-coating 510, gradually decreases from 2 at.% to 5 at.% to 0. In the direction away from the substrate, the V content in a single AlCrVN sub-coating gradually decreases from high to low in the gradient composite layer. On the one hand, the addition of V can improve the hardness and oxidation resistance of the functional coating, while the generated oxide VOx has a lubricating effect. On the other hand, the gradual decrease in V content is mainly aimed at transforming the crystal structure in the gradient composite layer from columnar to equiaxed crystals, eliminating stress concentration caused by the crystal transformation, and avoiding or suppressing cracking of the coating during use.

[0029] According to embodiments of this application, in the gradient composite layer 500, based on the total number of atoms in a single AlCrSiBN sub-coating 520, the atomic percentage of Si gradually increases from 0 to 3.5 at.% to 5 at.% in the direction away from the substrate; and in the gradient composite layer, based on the total number of atoms in a single AlCrSiBN sub-coating 520, the atomic percentage of B gradually increases from 0 to 1.5 at.% to 2.5 at.% in the direction away from the substrate. The gradual increase in Si and B in the AlCrSiBN sub-coatings from 0 in the direction away from the substrate generates an amorphous phase, further improving the surface hardness, toughness, and high-temperature stability.

[0030] According to embodiments of this application, the amorphous phase includes Si3N4 phase and BN phase.

[0031] According to an embodiment of this application, the gradient composite layer includes a nanocomposite structure, and the nanocomposite structure includes AlCrN grains coated with an amorphous phase.

[0032] The Si and B elements in the AlCrSiBN sub-coating can promote the formation of amorphous Si3N4 and BN phases, forming a nanocomposite structure (nc-AlCrN / a-Si3N4 / BN) to achieve a further significant improvement in hardness; in addition, the BN phase also has a certain lubricating effect and can react with VOCs. X The oxides form a synergistic self-lubricating effect.

[0033] According to embodiments of this application, in the direction away from the substrate, based on the total volume of the crystalline phase and the amorphous phase, the volume fraction of the amorphous phase in the gradient composite layer 500 continuously increases from 2%~5% to 12%~18%. The functional coating near the substrate has a low proportion of amorphous phase, retaining columnar crystals and ensuring toughness; the proportion of amorphous phase increases further away from the substrate, continuously refining the grains, inhibiting high-temperature grain growth, and improving the hardness of the functional coating; simultaneously, the amorphous phase can fill grain boundaries, hinder oxygen diffusion, and improve the coating's oxidation resistance.

[0034] In this application, the volume fraction of the amorphous phase can be calculated using ImageJ software from high-resolution transmission electron microscopy (HR-TEM) images.

[0035] According to an embodiment of this application, in the direction away from the substrate, the grain size in the crystal phase is continuously reduced from 50nm~80nm to 10nm~25nm.

[0036] In this application, the grain size can be calculated using the Debye-Scherrer method based on XRD patterns.

[0037] According to an embodiment of this application, in the gradient composite layer 500, in the AlCrSiBN sub-coating 520 adjacent to the AlCrTaN surface layer 600, based on the total number of atoms in a single AlCrSiBN sub-coating 520, the atomic percentage of Si is 3.5 at.% to 5 at.%, and the atomic percentage of B is 1.5 at.% to 2.5 at.%. The above-mentioned Si and B contents in the AlCrSiBN sub-coating adjacent to the AlCrTaN surface layer facilitate the full formation of Si3N4 and BN amorphous phases, thereby promoting good interface matching with the AlCrTaN surface layer, reducing interlayer interface stress, and ensuring interlayer bonding strength.

[0038] According to embodiments of this application, the thickness of the Cr adhesive layer 200 is 0.05 μm to 0.15 μm, specifically 0.05 μm, 0.07 μm, 0.1 μm, 0.13 μm, 0.15 μm, or any combination thereof. Within this range, the adhesive transition effect can be fully utilized, ensuring the wetting and bonding between the substrate and the subsequent CrN transition layer, without introducing additional internal stress due to excessive thickness.

[0039] According to an embodiment of this application, the thickness of the CrN transition layer 300 is 0.15 μm to 0.35 μm, specifically within the range of 0.15 μm, 0.20 μm, 0.25 μm, 0.30 μm, 0.35 μm, or any two thereof. Within this range, the physical property differences between the Cr bonding layer and the AlCrVN support layer are smoothly transitioned, alleviating interlayer stress.

[0040] According to embodiments of this application, the thickness of the AlCrVN support layer 400 is 0.5 μm to 1 μm, specifically within the range of 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, or any two thereof. Within this range, sufficient underlying toughness support can be provided.

[0041] According to an embodiment of this application, the AlCrVN support layer 400 has a columnar crystal structure. The columnar crystal structure of the AlCrVN support layer, with a phase structure of a solid solution of c-AlCrN and c-VN, is beneficial for giving the functional coating near the substrate good toughness.

[0042] According to an embodiment of this application, in the AlCrVN support layer 400, the atomic ratio between the metal elements Al, Cr and V is (60~68):(28~30):(4~10), and the atomic ratio between the metal elements Al, Cr and V and N satisfies: 0.9≤(Al+Cr+V) / N≤1.1; V element is fully dissolved into the AlCrN lattice to achieve solid solution strengthening; the atomic ratio of metal elements to nitrogen is close to 1, ensuring the stability of the nitride phase structure.

[0043] According to embodiments of this application, the thickness of the gradient composite layer 500 is 1 μm to 4 μm, specifically 1 μm, 2 μm, 3 μm, 4 μm, or any combination thereof. Within this range, the gradient structure can effectively leverage the gradual changes in composition, grain size, and thickness.

[0044] According to embodiments of this application, the thickness of each individual AlCrVN sub-coating 510 and each individual AlCrSiBN sub-coating 520 is independently 5 nm to 30 nm, specifically within the range of 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, or any two of these ranges. Within this range, the single-layer thickness of the sub-coating is at the nanoscale, which is beneficial for forming a coherent interface, achieving a fine-grained effect, and exerting the toughening effect of multi-layer interface deflection cracks.

[0045] According to embodiments of this application, the thickness of the AlCrTaN surface layer 600 is 0.3 μm to 0.5 μm, specifically 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, or any combination thereof. Within this range, it provides surface protection while also offering oxidation and wear resistance, without being too thick and causing excessive stress.

[0046] According to an embodiment of this application, the surface roughness Ra of the AlCrTaN surface layer on the side away from the substrate is less than 0.15 μm; the smooth surface of the AlCrTaN surface layer helps to reduce the coefficient of cutting friction.

[0047] In this application, the surface roughness Ra can be obtained by testing with an alicona instrument.

[0048] According to an embodiment of this application, the AlCrTaN surface layer 600 has an equiaxed crystal structure; the equiaxed crystal structure is isotropic, and its phase is c-AlCrN, which can suppress preferential oxidation of columnar grain boundaries.

[0049] According to an embodiment of this application, in the AlCrTaN surface layer 600, the atomic ratio between the metal elements Al, Cr and Ta is (60~68):(28~30):(6~15), and the atomic ratio between the metal elements and the N element satisfies: 0.9≤(Al+Cr+Ta) / N≤1.1; this helps to strengthen Ta through solid solution and improve high-temperature stability.

[0050] According to an embodiment of this application, in the functional coating, the region having a columnar crystal morphology is a columnar crystal region, and the total thickness of the columnar crystal region is 1 μm to 2 μm, specifically 1 μm, 1.5 μm, 2 μm, or any two of these ranges. Within this range, the film-substrate adhesion can be improved while maintaining good toughness of the functional coating.

[0051] According to embodiments of this application, in the functional coating, the region having an equiaxed crystal morphology is called an equiaxed crystal region, and the total thickness of the equiaxed crystal layer is 1μm to 4μm, specifically within the range of 1μm, 2μm, 3μm, 4μm, or any two thereof. Within the above range, the functional coating can possess good hardness, sufficient wear resistance, and high-temperature oxidation resistance.

[0052] According to embodiments of this application, the total thickness of the functional coating is 2μm to 6μm, specifically within the range of 2μm, 3μm, 4μm, 5μm, 6μm, or any two thereof. Within this range, both the protective capability of the functional coating and suitable internal stress can be achieved.

[0053] According to an embodiment of this application, the functional coating has a first end and a second end. The hardness of the surface of the first end monotonically increases from the surface of the second end, with the hardness of the first end surface being 28 GPa to 32 GPa and the hardness of the second end surface being 33 GPa to 37 GPa. The first end is the surface of the AlCrVN support layer away from the substrate, and the second end is the surface of the AlCrTaN surface layer away from the substrate. Thus, the hardness monotonically increases from the inside out, with the inner layer closer to the substrate exhibiting preferential toughness, and the surface layer farther from the substrate exhibiting preferential hardness.

[0054] In this application, the hardness of the first end surface is tested as follows: a Cr bonding layer, a CrN transition layer and an AlCrVN support layer are formed sequentially on the substrate, and the hardness is tested using a nanoindenter.

[0055] The hardness test method for the second end surface is as follows: A Cr bonding layer, a CrN transition layer, an AlCrVN support layer, a gradient composite layer, and an AlCrTaN surface layer are sequentially formed on the substrate, and the hardness is tested using a nanoindenter. The process parameters, thickness, composition, and other physical properties of the Cr bonding layer, CrN transition layer, and AlCrVN support layer are consistent with those of the first end test sample.

[0056] According to an embodiment of this application, the fracture toughness of the functional coating is 4.5 MPa·m. 1 / 2 ~5.5 MPa·m 1 / 2 Specifically, such as 4.5 MPa·m 1 / 2 4.7 MPa·m 1 / 2 4.9 MPa·m 1 / 2 5.0 MPa·m 1 / 2 5.3 MPa·m 1 / 2 5.5 MPa·m 1 / 2or a range between either or both. Within the aforementioned range, the functional coating exhibits good resistance to crack propagation and is not easily cracked or peeled off when subjected to cutting impacts.

[0057] In this application, the fracture toughness of the functional coating can be obtained by Vickers indentation test and by measuring the crack length.

[0058] A second aspect of this application provides a method for preparing the composite-coated cutting tool described in the first aspect, comprising: S10: Provides the matrix.

[0059] According to an embodiment of this application, the substrate can be sandblasted, cleaned, and dried before being placed on a rotating rack for glow discharge cleaning of the substrate surface.

[0060] S20: In a pure Ar atmosphere, using a pure Cr target as the deposition source, a Cr binder layer is deposited on the surface of the substrate to obtain the first product.

[0061] In this step, Ar ions bombard the substrate surface in a pure Ar atmosphere while simultaneously depositing a metallic Cr layer. The metallic Cr and the substrate form good wettability, resulting in a metallic Cr bond layer and yielding the first product.

[0062] According to embodiments of this application, the temperature for depositing the Cr binder layer is 450℃~550℃, specifically 450℃, 470℃, 490℃, 500℃, 510℃, 530℃, 550℃, or any range between two of these. Within this range, Cr atoms are better able to spread and wet the substrate surface, forming a continuous and dense metallic Cr binder layer, ensuring a good interfacial bond between the binder layer and the substrate.

[0063] According to embodiments of this application, the bias voltage of the deposited Cr binder layer is -120V to -180V, specifically -120V, -130V, -140V, -150V, -160V, -170V, -180V, or any range between two of these. Within this range, the substrate surface can obtain suitable ion bombardment energy, promoting a strong bond between the deposited Cr atoms and the substrate, which is beneficial for improving the density of the Cr binder layer and the film-substrate bonding strength.

[0064] According to embodiments of this application, during the deposition of the Cr binder layer, the pure Cr target current is 130A to 160A, specifically 130A, 140A, 150A, 160A, or any combination thereof. Within this range, the pure Cr target can maintain a stable sputtering rate, achieving a stable and continuous supply of Cr atoms, facilitating precise control of the deposition rate and thickness of the Cr binder layer, resulting in a Cr binder layer with uniform thickness and composition.

[0065] According to embodiments of this application, the gas pressure of the deposited Cr binder layer is 0.2 Pa to 1.0 Pa, specifically within the ranges of 0.2 Pa, 0.3 Pa, 0.4 Pa, 0.5 Pa, 0.6 Pa, 0.7 Pa, 0.8 Pa, 0.9 Pa, 1.0 Pa, or any two of these ranges. Within these ranges, it helps the generated Cr atoms to uniformly reach all areas of the substrate, ensuring the overall uniformity and density of the Cr binder layer.

[0066] S30: In a pure N2 atmosphere, using a pure Cr target as the deposition source, a CrN transition layer is deposited on the surface of the first product to obtain the second product.

[0067] This step switches to a pure N2 atmosphere, where Cr atoms sputtered from the Cr target react with N2 to generate CrN, forming a CrN transition layer on the surface of the Cr binder layer. This completes the transition from the metal layer to the nitride coating, mitigating the abrupt change in interfacial properties and yielding the second product.

[0068] According to embodiments of this application, the temperature for depositing the CrN transition layer is 450℃~550℃, specifically 450℃, 470℃, 490℃, 500℃, 510℃, 530℃, 550℃, or any range between two of these. Within this range, Cr atoms and nitrogen molecules possess suitable reactivity, which is conducive to the full formation of Cr-N chemical bonds, promotes the formation of a CrN phase with excellent crystal quality, and ensures a dense and complete CrN transition layer structure.

[0069] According to embodiments of this application, the bias voltage of the deposited CrN transition layer is -40V to -60V, specifically -40V, -45V, -50V, -55V, -60V, or any two of these ranges. Within this range, the Cr binder layer receives moderate ion bombardment, which is beneficial for improving the density of the CrN transition layer while maintaining good interfacial bonding between the Cr binder layer and the CrN transition layer.

[0070] According to an embodiment of this application, during the deposition of the CrN transition layer, the target current of the pure Cr target is 130A to 160A, specifically 130A, 140A, 150A, 160A, or any combination thereof. Within this range, the pure Cr target can provide a stable number of Cr atoms, facilitating controllable growth of the CrN transition layer thickness and obtaining a uniformly thick transition layer film.

[0071] According to embodiments of this application, the gas pressure for depositing the CrN transition layer is 2.5 Pa to 4.0 Pa, specifically within the ranges of 2.5 Pa, 2.8 Pa, 3.0 Pa, 3.2 Pa, 3.5 Pa, 3.8 Pa, 4.0 Pa, or any two of these ranges. Within these ranges, the nitrogen plasma discharge conditions are stable, and the nitrogen source supply is sufficient, ensuring a complete nitriding reaction of Cr atoms, which is beneficial for generating a CrN transition layer with uniform composition and stable structure.

[0072] S40: In a pure N2 atmosphere, using an AlCrV target as the deposition source, an AlCrVN support layer is deposited on the surface of the second product to obtain the third product.

[0073] This step uses an AlCrV alloy target to sputter and deposit an AlCrVN nitride support layer under a nitrogen atmosphere, forming a columnar AlCrVN support layer. The V element dissolves into the AlCrN lattice, which plays a role in solid solution strengthening, and the third product is obtained.

[0074] According to embodiments of this application, the deposition temperature of the AlCrVN support layer is 450℃~550℃, specifically 450℃, 470℃, 490℃, 500℃, 510℃, 530℃, 550℃, or any range between two of these. Within this range, the sputtered Al, Cr, and V atoms possess suitable reactive diffusion capabilities, allowing them to fully undergo nitriding reactions with the nitrogen source, which is beneficial for forming a fully crystalline AlCrVN support layer and ensuring its good toughness.

[0075] According to embodiments of this application, the bias voltage of the deposited AlCrVN support layer is -40V to -60V, specifically -40V, -45V, -50V, -55V, -60V, or any range between two of these. Within this range, the CrN transition layer is subjected to moderate ion bombardment, promoting directional grain growth and increasing the density of the AlCrVN support layer.

[0076] According to embodiments of this application, during the deposition of the AlCrVN support layer, the AlCrV target current is 150A~200A, specifically 150A, 160A, 170A, 180A, 190A, 200A, or any combination thereof. Within this range, the AlCrV alloy target sputtering is stable, allowing for the output of metal atoms with stable composition, facilitating controllable deposition of the support layer thickness and obtaining a uniformly composed AlCrVN support layer.

[0077] According to embodiments of this application, the gas pressure for depositing the AlCrVN support layer is 2.5 Pa to 4.0 Pa, specifically within the ranges of 2.5 Pa, 2.8 Pa, 3.0 Pa, 3.2 Pa, 3.5 Pa, 3.8 Pa, 4.0 Pa, or any two of these ranges. Within these ranges, the nitrogen plasma operates stably, and the nitrogen supply is sufficient, which is conducive to the complete nitridation of Al, Cr, and V metal atoms, resulting in a stable and dense AlCrVN support layer.

[0078] S50: In a pure N2 atmosphere, using AlCrV and AlCrSiB targets as deposition sources, the AlCrV and AlCrSiB targets are deposited alternately, and the target current of the AlCrV target is gradually reduced until it is turned off, while the target current of the AlCrSiB target is gradually increased, and the deposition bias voltage is gradually increased. Through the alternating deposition of the AlCrV and AlCrSiB targets, AlCrVN sub-coatings and AlCrSiBN sub-coatings are sequentially formed, and the AlCrVN sub-coatings and AlCrSiBN sub-coatings constitute a gradient composite layer to obtain the fourth product.

[0079] This step involves dual-target co-sputtering, where the AlCrV target current is gradually decreased and the AlCrSiB target current is gradually increased, resulting in a gradual decrease in V content and a gradual increase in Si and B content. Simultaneously, the bias voltage is gradually increased to enhance ion bombardment energy and promote grain refinement. AlCrVN and AlCrSiBN sub-coatings are stacked alternately through alternating deposition. Furthermore, as the target current changes, the thickness of the AlCrVN sub-coating layer gradually decreases, while the thickness of the AlCrSiBN sub-coating layer gradually increases, resulting in a gradient composite layer, i.e., the fourth product.

[0080] According to an embodiment of this application, in a pure N2 atmosphere, using AlCrV and AlCrSiB targets as deposition sources, the AlCrV and AlCrSiB targets are deposited alternately, and the bias voltage is controlled to increase linearly from -60 to -80V to -100 to -120V. The target current of the AlCrV target decreases linearly from 150A to 200A to 50A and is then turned off; the target current of the AlCrSiB target increases linearly from 50A to 150 to 200A and is then normally turned on, resulting in a fourth product.

[0081] As a result, the bias voltage increases linearly, the ion bombardment energy continues to increase, and the grains are continuously refined; the target current of AlCrV decreases linearly to achieve a continuous decrease in the proportion of V atoms; the target current of AlCrSiB increases linearly to achieve a continuous increase in the proportion of Si and B atoms; the linear change in current ensures a continuous gradient of composition and avoids or reduces the interfacial stress caused by abrupt changes in composition.

[0082] According to an embodiment of this application, after obtaining the fourth product, the process further includes Ar ion etching on the surface of the AlCrSiBN sub-coating for a time of 5 min to 10 min.

[0083] Therefore, Ar ion etching bombards the surface of the gradient composite layer, blocking the transmission of surface roughness from the lower layer near the substrate to the upper layer, effectively reducing the surface roughness of the AlCrTaN layer and decreasing the interfacial friction coefficient between the composite coating tool and the workpiece.

[0084] S60: In a pure N2 atmosphere, using an AlCrTa target as the deposition source, an AlCrTaN surface layer is deposited on the surface of the fourth product to obtain a composite coated cutting tool.

[0085] This step uses an AlCrTa alloy target to deposit an AlCrTaN surface layer under a nitrogen atmosphere. Ta dissolves into the AlCrN lattice to form the surface layer, thus completing the final composite coating tool preparation.

[0086] According to embodiments of this application, the deposition temperature of the AlCrTaN surface layer is 450℃~550℃, specifically 450℃, 470℃, 490℃, 500℃, 510℃, 530℃, 550℃, or any range between two of these. Within this range, Al, Cr, and Ta metal atoms possess suitable reactivity, enabling them to react fully with N2, which facilitates the formation of a stable AlCrTaN nitride, ensuring the surface layer has a good high-temperature oxidation resistance.

[0087] According to embodiments of this application, the bias voltage of the deposited AlCrTaN surface layer is -80V to -120V, specifically -80V, -90V, -100V, -110V, -120V, or any range between two of these. Within this range, higher ion bombardment energy can effectively refine the grains, promote the formation of isotropic equiaxed crystal structures, and improve the density of the AlCrTaN surface layer.

[0088] According to embodiments of this application, during the deposition of the AlCrTaN surface layer, the target current of the AlCrTa target is 150A~200A, specifically 150A, 160A, 170A, 180A, 190A, 200A, or any two of these ranges. Within this range, the AlCrTa target sputtering output is stable, the atomic ratios of the various metal components remain stable, enabling uniform growth of the AlCrTaN surface layer, facilitating precise control of the surface layer thickness, and resulting in a protective surface layer with uniform composition.

[0089] According to embodiments of this application, the gas pressure for depositing the AlCrTaN surface layer is 2.5 Pa to 4.0 Pa, specifically within the ranges of 2.5 Pa, 2.8 Pa, 3.0 Pa, 3.2 Pa, 3.5 Pa, 3.8 Pa, 4.0 Pa, or any two of these ranges. Within these ranges, the plasma discharge is stable, and the nitrogen supply is sufficient, ensuring complete nitriding of Al, Cr, and Ta metal atoms, which is beneficial for obtaining a dense AlCrTaN surface layer with excellent overall performance.

[0090] The embodiments of this application are described in detail below.

[0091] Example 1 A method for preparing a composite coated cutting tool, using an arc ion plating process, includes the following steps: (1) Using carbide cutting tools as the substrate, the substrate is sandblasted, cleaned and dried and then placed on a rotating frame to perform glow discharge cleaning on the surface of the substrate. (2) A Cr binder layer is deposited on the substrate, with the following process parameters: The temperature was 450℃, the bias voltage was -120V, the target current of the pure Cr target was 130A, the gas pressure was 0.5Pa, and the gas was pure Ar; the thickness of the Cr bonding layer was 0.1μm. (3) A CrN transition layer is deposited on the surface of the Cr bonding layer, with the following process parameters: The temperature was 450℃, the bias voltage was -40V, the target current of the pure Cr target was 130A, the gas pressure was 3.0Pa, and the gas was pure N2; the thickness of the CrN transition layer was 0.2μm. (4) An AlCrVN support layer is deposited on the surface of the CrN transition layer. The process parameters are as follows: The temperature is 450℃, the bias voltage is -60V, the AlCrV target current is 150A, the gas pressure is 2.5Pa, and the gas is pure N2; the thickness of the AlCrVN support layer is 0.8μm; the atomic ratio between the metal elements in the AlCrVN support layer is Al:Cr:V = 67:25:8. (5) A gradient composite layer is deposited on the surface of the AlCrVN support layer, with the following process parameters: At a temperature of 450℃, AlCrV and AlCrSiB targets were deposited alternately. The bias voltage was controlled to increase linearly from -60V to -100V, while the AlCrV target current was linearly decreased from 150A to 50A and then turned off; the AlCrSiB target current was linearly increased from 50A to 150A and then turned on normally. The gas pressure was 3.0 Pa, and the gas was pure N2. Under these conditions, AlCrVN sub-coatings (thickness decreased from 20nm to 5nm) and AlCrSiBN sub-coatings (thickness increased from 5nm to 20nm) were formed sequentially. The AlCrVN sub-coating is deposited on the surface of the AlCrVN support layer. Throughout the gradient composite layer, the atomic percentage of V gradually decreases from 4 at.% to 0; the atomic percentage of Si gradually increases from 0 to 3.5 at.%; and the atomic percentage of B gradually increases from 0 to 2 at.% (i.e., the atomic percentage of Si in the last AlCrSiBN sub-coating is 3.5 at.% and the atomic percentage of B is 2 at.%). The grain size continuously decreases from 80 nm in the first sub-coating to 15 nm in the last sub-coating. (6) Ar ion etching was performed on the surface of the AlCrSiBN sub-coating of the gradient composite layer for 6 min; (7) An AlCrTaN surface layer is deposited on the AlCrSiBN sub-coating surface of the gradient composite layer. The process parameters are as follows: The temperature is 450℃, the bias voltage is -80V, the target current of AlCrTa is 150A, the gas pressure is 2.5Pa, and the gas is pure N2; the thickness of the AlCrTaN surface layer is 0.3μm; the atomic ratio between the metal elements in the AlCrTaN surface layer is Al:Cr:Ta = 65:30:5. (8) After the temperature drops to room temperature, the sample is taken out to obtain a high-temperature self-lubricating wear-resistant coated tool.

[0092] Example 2 A method for preparing a composite coated cutting tool, using an arc ion plating process, includes the following steps: (1) Using carbide cutting tools as the substrate, the substrate is sandblasted, cleaned and dried and then placed on a rotating frame to perform glow discharge cleaning on the surface of the substrate. (2) A Cr binder layer is deposited on the substrate, with the following process parameters: The temperature was 500℃, the bias voltage was -150V, the target current of the pure Cr target was 140A, the gas pressure was 0.5Pa, and the gas was pure Ar; the thickness of the Cr bonding layer was 0.13μm. (3) A CrN transition layer is deposited on the surface of the Cr bonding layer, with the following process parameters: The temperature was 500℃, the bias voltage was -50V, the target current of the pure Cr target was 140A, the gas pressure was 3.0Pa, and the gas was pure N2; the thickness of the CrN transition layer was 0.28μm. (4) An AlCrVN support layer is deposited on the surface of the CrN transition layer. The process parameters are as follows: The temperature is 550℃, the bias voltage is -50V, the target current of the AlCrV target is 170A, the gas pressure is 3.0Pa, and the gas is pure N2; the thickness of the AlCrVN support layer is 0.7μm; the atomic ratio between the metal elements in the AlCrVN support layer is Al:Cr:V = 63:29:8. (5) A gradient composite layer is deposited on the surface of the AlCrVN support layer, with the following process parameters: At a temperature of 500℃, AlCrV and AlCrSiB targets were deposited alternately. The bias voltage was controlled to increase linearly from -60V to -100V. The target current of the AlCrV target decreased linearly from 170A to 50A and then was turned off. The target current of the AlCrSiB target increased linearly from 50A to 170A and then was normally turned on. The gas pressure was 3.5 Pa, and the gas was pure N2. Under the above conditions, an AlCrVN sub-coating (thickness decreased from 25 nm to 5 nm) and an AlCrSiBN sub-coating (thickness increased from 5 nm to 25 nm) were formed sequentially, with the AlCrVN sub-coating deposited on the surface of the AlCrVN support layer. In the entire gradient composite layer, the atomic percentage of V gradually decreased from 4 at.% to 0; the atomic percentage of Si gradually increased from 0 to 4.5 at.%; and the atomic percentage of B gradually increased from 0 to 1.5 at.% (i.e., the atomic percentage of Si in the last AlCrSiBN sub-coating was 4.5 at.% and the atomic percentage of B was 1.5 at.%). The grain size continuously decreased from 70 nm in the first sub-coating to 13 nm in the last sub-coating. (6) Ar ion etching was performed on the surface of the AlCrSiBN sub-coating of the gradient composite layer for 7 min; (7) An AlCrTaN surface layer is deposited on the AlCrSiBN sub-coating surface of the gradient composite layer. The process parameters are as follows: The temperature is 550℃, the bias voltage is -100V, the target current of the AlCrTa target is 170A, the gas pressure is 3.0Pa, and the gas is pure N2; the thickness of the AlCrTaN surface layer is 0.4μm; and the atomic ratio between the metal elements in the AlCrTaN surface layer is Al:Cr:Ta = 60:30:10. (8) After the temperature drops to room temperature, the sample is taken out to obtain a high-temperature self-lubricating wear-resistant coated tool.

[0093] Example 3 A method for preparing a composite coated cutting tool, using an arc ion plating process, includes the following steps: (1) Using carbide cutting tools as the substrate, the substrate is sandblasted, cleaned and dried and then placed on a rotating frame to perform glow discharge cleaning on the surface of the substrate. (2) A Cr binder layer is deposited on the substrate, with the following process parameters: The temperature was 550℃, the bias voltage was -180V, the target current of the pure Cr target was 160A, the gas pressure was 0.8Pa, and the gas was pure Ar; the thickness of the Cr bonding layer was 0.11μm. (3) A CrN transition layer is deposited on the surface of the Cr bonding layer, with the following process parameters: The temperature was 550℃, the bias voltage was -60V, the target current of the pure Cr target was 160A, the gas pressure was 2.5Pa, and the gas was pure N2; the thickness of the CrN transition layer was 0.32μm. (4) An AlCrVN support layer is deposited on the surface of the CrN transition layer. The process parameters are as follows: The temperature is 550℃, the bias voltage is -60V, the AlCrV target current is 200A, the gas pressure is 4.0Pa, and the gas is pure N2; the thickness of the AlCrVN support layer is 1μm; the atomic ratio between the metal elements in the AlCrVN support layer is Al:Cr:V=60:30:10. (5) A gradient composite layer is deposited on the surface of the AlCrVN support layer, with the following process parameters: At a temperature of 550℃, AlCrV and AlCrSiB targets were deposited alternately. The bias voltage was controlled to increase linearly from -60V to -120V. The AlCrV target current decreased linearly from 200A to 50A and then was turned off. The AlCrSiB target current increased linearly from 50A to 200A and then was normally turned on. The gas pressure was 4.5 Pa, and the gas was pure N2. Under the above conditions, an AlCrVN sub-coating (thickness decreased from 30 nm to 5 nm) and an AlCrSiBN sub-coating (thickness increased from 5 nm to 30 nm) were formed sequentially, with the AlCrVN sub-coating deposited on the surface of the AlCrVN support layer. In the entire gradient composite layer, the atomic percentage of V gradually decreased from 5 at.% to 0; the atomic percentage of Si gradually increased from 0 to 4.5 at.%; and the atomic percentage of B gradually increased from 0 to 2.5 at.% (i.e., the atomic percentage of Si in the last AlCrSiBN sub-coating was 4.5 at.% and the atomic percentage of B was 2.5 at.%). The grain size continuously decreased from 80 nm in the first sub-coating to 10 nm in the last sub-coating. (6) Ar ion etching was performed on the surface of the AlCrSiBN sub-coating of the gradient composite layer for 10 min; (7) An AlCrTaN surface layer is deposited on the AlCrSiBN sub-coating surface of the gradient composite layer. The process parameters are as follows: The temperature is 550℃, the bias voltage is -120V, the target current of the AlCrTa target is 200A, the gas pressure is 4.0Pa, and the gas is pure N2; the thickness of the AlCrTaN surface layer is 0.5μm; the atomic ratio between the metal elements in the AlCrTaN surface layer is Al:Cr:Ta = 60:27:13. (8) After the temperature drops to room temperature, the sample is taken out to obtain a high-temperature self-lubricating wear-resistant coated tool.

[0094] Comparative Example 1 The difference from Example 3 is that no gradient composite layer and AlCrTaN surface layer are deposited; that is, only a Cr binder layer, a CrN transition layer and an AlCrVN support layer are present. The coating time of the remaining layers will be extended to the AlCrVN support layer, so that the total thickness of the functional coating in Comparative Example 1 is the same as that in Example 3.

[0095] Comparative Example 2 The difference from Example 3 is that in step (5), AlCr target is used instead of AlCrV target and AlCrSiB target for alternating deposition, that is, the gradient composite layer is AlCrN sublayer and AlCrSiBN sublayer.

[0096] Comparative Example 3 The difference from Example 3 is that in step (5), the AlCrV target and AlCrSiB target are used with a constant target current of 200A and a constant bias voltage of -80V, without linear gradient. That is, it has an alternating structure but does not contain a triple gradient structure.

[0097] Comparative Example 4 The difference from Example 3 is that no AlCrTaN surface layer is deposited.

[0098] Comparative Example 5 The difference from Example 3 is that the coating is an AlTiN coating prepared by conventional arc ion plating, and the deposition parameters are: The temperature was 500℃, the bias voltage was -80V, the target current of the AlTi target was 200A, the gas pressure was 4Pa, and the gas was pure N2; the coating thickness was the same as in Example 3.

[0099] The performance of the cutting tools prepared in the above embodiments and comparative examples was tested, and the results are shown in Table 1.

[0100] (1) The performance and milling tests of the composite coated cutting tools prepared by the above embodiments and comparative examples are as follows: Material: TC18 titanium alloy; Tool type: RPHT 1204M8E-MM3; Cutting conditions: cutting speed 60m / min, feed rate 0.4mm / z, depth of cut 1.0mm; The wear amount VB (unit mm) of the tool flank face after different cutting times is shown in Table 1. The wear amount of the tool flank face was measured using an OLYMPUS-SZ61 optical ultra-depth-of-field microscope with a graduated scale.

[0101] (2) Atomic percentage of elements: obtained by electron probe microanalysis (EPMA).

[0102] (3) Grain size: Calculated by the Debye-Scherrer method based on XRD patterns.

[0103] (4) The test method for the bonding strength (film-substrate adhesion) between the functional coating and the substrate is as follows: The bonding strength between the functional coating and the substrate is measured using the REVETEST scratch tester manufactured by CSM, Switzerland. The scratch test method involves sliding a hemispherical diamond indenter with a diameter of approximately 200 micrometers on the surface of the functional coating. During this process, the vertical load L is continuously increased by an automatic loading mechanism. When L reaches its critical load Lc, the test is continued until the critical load Lc is reached. c At this point, the functional coating begins to peel off from the tool substrate, and the critical interfacial load L between the functional coating and the substrate... c The minimum load required for the indenter to completely penetrate the functional coating and continuously peel it off from the substrate is defined as follows: Simultaneously, the frictional force F between the indenter, the functional coating, and the substrate changes accordingly. At this point, the functional coating generates acoustic emission. Sensors acquire the acoustic emission signals during the scratching process, the change in load, and the change in tangential force. These signals are amplified, processed, and input into a computer. After A / D conversion, the measurement results are plotted graphically, and the critical load value L is plotted on the acoustic emission signal-load curve. c The corresponding acoustic emission peak is obtained at this point, and the critical load L is at this point. c This serves as the criterion for judging the bonding strength between the functional coating and the substrate. The test parameters are: linear loading, load 200N, loading rate 99N / min, scratching speed 5mm / min, and scratch length 5mm.

[0104] (5) Overall hardness measurement method of functional coating: The nanohardness (H) of the functional coating was measured using a nanoindenter (Anton Paar, TTX-NHT2). The maximum load applied during the nanoindentation test was 20 mN to ensure that the indentation depth of the indenter did not exceed 1 / 10 of the thickness of the functional coating. All measurements were performed on the surface of the functional coating AlCrTaN, with 20 measurement points tested on the AlCrTaN surface; the average value was taken as the overall hardness value of the functional coating.

[0105] (6) Coating fracture toughness (K) ICMeasurement Method: The fracture toughness of the coating was evaluated using a Vickers indentation test with a diamond indenter and a load of 1000 mN. The fracture toughness of the coating was characterized by the length of the crack originating from the indentation angle. The morphology of the Vickers diamond indenter was measured using scanning electron microscopy (SEM). The calculation formula is as follows: Where A is a constant of 0.028, HV is nanohardness (HV), P is the load (kg), and l i The crack length (mm) is the indentation angle.

[0106] Table 1

[0107] As can be seen from Table 1, under the same cutting conditions, the cutting performance of the high-temperature self-lubricating wear-resistant coated tool of this application is better than that of the comparative example.

[0108] The above embodiments represent slow, normal wear, which is an ideal failure mode; however, several comparative examples show sudden failures: chipping, coating peeling, and severe adhesive wear, which are abnormal premature failures, resulting in sudden damage to the tool.

[0109] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this invention and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.

[0110] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0111] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0112] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A composite coated cutting tool, characterized in that, include: A substrate and a functional coating disposed on the surface of the substrate, the functional coating comprising: A Cr adhesive layer is disposed on the surface of the substrate; A CrN transition layer is disposed on the surface of the Cr adhesive layer away from the substrate; An AlCrVN support layer is disposed on the surface of the CrN transition layer away from the substrate; A gradient composite layer includes multiple stacked sub-coatings, each of which includes an AlCrVN sub-coating and an AlCrSiBN sub-coating, wherein the AlCrVN sub-coating is disposed close to the AlCrVN support layer; An AlCrTaN surface layer is disposed on the surface of the gradient composite layer away from the substrate; Wherein, in the direction away from the substrate, the gradient composite layer satisfies: The atomic percentage of V gradually decreases; The atomic percentages of Si and B each increase gradually and independently; The crystal morphology transitions continuously from columnar to equiaxed crystals, and the volume fraction of the amorphous phase gradually increases. The thickness of a single layer of the AlCrVN sub-coating gradually decreases; The thickness of the single layer of the AlCrSiBN sub-coating gradually increases; The volume fraction of the amorphous phase is calculated based on the total volume fraction of the crystalline phase and the amorphous phase.

2. The composite coated cutting tool according to claim 1, characterized in that, At least one of the following conditions must be met: In the direction away from the substrate, in the gradient composite layer, the atomic percentage of V, calculated based on the total number of atoms in a single AlCrVN sub-coating, gradually decreases from 2 at.% to 5 at.% to 0. In the direction away from the substrate, in the gradient composite layer, the atomic percentage of Si gradually increases from 0 to 3.5 at.%~5 at.% based on the total number of atoms in a single AlCrSiBN sub-coating. In the direction away from the substrate, in the gradient composite layer, the atomic percentage of B gradually increases from 0 to 1.5 at.% to 2.5 at.%, based on the total number of atoms in a single AlCrSiBN sub-coating.

3. The composite coated cutting tool according to claim 1, characterized in that, At least one of the following conditions must be met: The amorphous phase includes Si3N4 phase and BN phase; In the direction away from the matrix, based on the total volume of the crystalline phase and the amorphous phase, the volume fraction of the amorphous phase in the gradient composite layer continuously increases from 2%~5% to 12%~18%; In the direction away from the matrix, the grain size in the crystalline phase decreases continuously from 50 nm to 80 nm to 10 nm to 25 nm; The gradient composite layer includes a nanocomposite structure, and the nanocomposite structure includes AlCrN grains coated with an amorphous phase.

4. The composite coated cutting tool according to claim 1, characterized in that, At least one of the following conditions must be met: The thickness of the Cr bonding layer is 0.05 μm to 0.15 μm; The thickness of the CrN transition layer is 0.15 μm to 0.35 μm; The thickness of the AlCrVN support layer is 0.5μm~1μm; The thickness of the gradient composite layer is 1μm~4μm; The thickness of each AlCrVN sub-coating and each AlCrSiBN sub-coating is independently 5 nm to 30 nm; The thickness of the AlCrTaN surface layer is 0.3 μm to 0.5 μm.

5. The composite coated cutting tool according to claim 1, characterized in that, At least one of the following conditions must be met: The AlCrVN support layer has a columnar crystal structure; In the AlCrVN support layer, the atomic ratio between the metal elements Al, Cr and V is (60~68):(28~30):(4~10), and the atomic ratio between the metal elements Al, Cr and V and N satisfies: 0.9≤(Al+Cr+V) / N≤1.1; The surface roughness Ra of the AlCrTaN surface layer on the side away from the substrate is less than 0.15 μm; The surface layer of AlCrTaN has an equiaxed crystal structure; In the AlCrTaN surface layer, the atomic ratio between the metal elements Al, Cr and Ta is (57~68):(24~30):(6~15), and the atomic ratio between the metal elements and the N element satisfies: 0.9≤(Al+Cr+Ta) / N≤1.1; In the gradient composite layer, in the AlCrSiBN sub-coating adjacent to the AlCrTaN surface layer, based on the total number of atoms in a single AlCrSiBN sub-coating, the atomic percentage of Si is 3.5 at.% to 5 at.%, and the atomic percentage of B is 1.5 at.% to 2.5 at.%.

6. The composite coated cutting tool according to claim 1, characterized in that, At least one of the following conditions must be met: In the functional coating, the region with columnar crystal morphology is called the columnar crystal region, and the total thickness of the columnar crystal region is 1μm~2μm; In the functional coating, the region with equiaxed crystal morphology is called the equiaxed crystal region, and the total thickness of the equiaxed crystal region is 1μm~4μm; The total thickness of the functional coating is 2μm~6μm; The fracture toughness of the functional coating is 4.5 MPa·m. 1 / 2 ~5.5 MPa·m 1 / 2 ; The functional coating has a first end and a second end, the hardness of the surface of the first end increases monotonically from the hardness of the surface of the second end, and the hardness of the surface of the first end is 28GPa~32GPa, and the hardness of the surface of the second end is 33GPa~37GPa. The first end is the surface of the AlCrVN support layer away from the substrate, and the second end is the surface of the AlCrTaN surface layer away from the substrate.

7. A method for preparing the composite coated cutting tool according to any one of claims 1 to 6, characterized in that, include: Provide a matrix; In a pure Ar atmosphere, using a pure Cr target as the deposition source, a Cr binder layer is deposited on the surface of the substrate to obtain the first product. In a pure N2 atmosphere, using a pure Cr target as the deposition source, a CrN transition layer is deposited on the surface of the first product to obtain the second product; In a pure N2 atmosphere, using an AlCrV target as the deposition source, an AlCrVN support layer is deposited on the surface of the second product to obtain the third product. In a pure N2 atmosphere, using AlCrV and AlCrSiB targets as deposition sources, the AlCrV and AlCrSiB targets are deposited alternately while the target current of the AlCrV target is gradually reduced until it is turned off, and the target current of the AlCrSiB target is gradually increased, along with the deposition bias voltage. Through the alternating deposition of the AlCrV and AlCrSiB targets, AlCrVN and AlCrSiBN sub-coatings are sequentially formed, forming a gradient composite layer to obtain the fourth product. In a pure N2 atmosphere, using an AlCrTa target as the deposition source, an AlCrTaN surface layer is deposited on the surface of the fourth product to obtain a composite coated tool.

8. The method according to claim 7, characterized in that, In a pure N2 atmosphere, using AlCrV and AlCrSiB targets as deposition sources, the AlCrV and AlCrSiB targets are deposited alternately, and the bias voltage is controlled to increase linearly from -60V to -80V to -100V to -120V. The target current of the AlCrV target decreases linearly from 150A to 200A to 50A and then is turned off; the target current of the AlCrSiB target increases linearly from 50A to 150A to 200A and then is turned on normally, yielding the fourth product.

9. The method according to claim 7, characterized in that, At least one of the following conditions must be met: The temperature at which the Cr bonding layer is deposited is 450℃~550℃; The bias voltage of the deposited Cr bonding layer is -120V to -180V; When depositing the Cr binder layer, the target current of the pure Cr target is 130A~160A; The gas pressure of the deposited Cr binder layer is 0.2 Pa to 1.0 Pa; The temperature at which the CrN transition layer is deposited is 450℃~550℃; The bias voltage of the deposited CrN transition layer is -40V to -60V; When depositing the CrN transition layer, the target current of the pure Cr target is 130A~160A; The gas pressure of the deposited CrN transition layer is 2.5 Pa to 4.0 Pa; The temperature at which the AlCrVN support layer is deposited is 450℃~550℃; The bias voltage of the deposited AlCrVN support layer is -40V to -60V; When depositing the AlCrVN support layer, the AlCrV target current is 150A~200A; The gas pressure of the deposited AlCrVN support layer is 2.5 Pa to 4.0 Pa; The temperature at which the AlCrTaN surface layer is deposited is 450℃~550℃; The bias voltage of the deposited AlCrTaN surface layer is -80V to -120V; When depositing the AlCrTaN surface layer, the target current of the AlCrTa target is 150A~200A; The gas pressure of the deposited AlCrTaN surface layer is 2.5 Pa to 4.0 Pa.

10. The method according to claim 7, characterized in that, After obtaining the fourth product, the process further includes Ar ion etching on the surface of the AlCrSiBN sub-coating for 5 min to 10 min.